PENGARUH INDUSTRI KECIL, TENAGA KERJA, DAN KREDIT TERHADAP PDRB DI KARESIDENAN KEDU TAHUN 2014-2018 - Leganing Adistia Putri; Rr. Retno Sugiharti (Universitas Teuku Umar, 2020)
This study aims to see how much influence the small industry, labor, and credit scores have on the PDRB in the Kedu Residency. This research uses a quantitative approach, by taking the object of research in the Kedu Residency Area within five years, namely in 2014-2018. The dependent variable in this study is the PDRB in the Kedu Residency Area and the independent variable of this study is the number of small industries, the number of workers, and credit. The rate of PDRB growth in the manufacturing sector and growth in the small industrial sector in the residency of Kedu tends to fluctuate. Considering that the majority of the processing industries in the Kedu residency are small industries, it can be said that the management of the potential of small industries in the Kedu Residency has not been explored properly. The results of this study indicate that the distribution of funds in the form of granting loans / credit significantly influences the PDRB in the Kedu Residency, while the number of small industries and labor does not significantly influence the PDRB in the Kedu Residency.Keywords : Industry, labor, PDRB, Kedu Residency